2014
DOI: 10.1177/0003319714548211
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Fat Tissue Predicts Increased Long-Term Major Adverse Cardiac Event in Patients With Moderate Cardiovascular Risk

Abstract: We investigated the relationship between epicardial fat volume (EFV) measured by multislice computed tomography (MDCT) and long-term major adverse cardiac events (MACEs). Consecutive patients (n = 564) were enrolled in this retrospective study. Patients were divided into tertiles according to EFV. Patients were followed up for an average of 18 months. Patients in each tertile were similar in terms of gender and risk factors. Patients with greater EFV in the third group were more likely to be overweight (P = .0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…29 Epicardial fat predicts increased long-term major adverse cardiac events in patients with moderate CV risk. 30 The role of cardiac adiposity in fatty liver has not been thoroughly explored. Studies with inconsistent results exist in the literature.…”
Section: Epicardial Adipose Tissue In Nafldmentioning
confidence: 99%
“…29 Epicardial fat predicts increased long-term major adverse cardiac events in patients with moderate CV risk. 30 The role of cardiac adiposity in fatty liver has not been thoroughly explored. Studies with inconsistent results exist in the literature.…”
Section: Epicardial Adipose Tissue In Nafldmentioning
confidence: 99%
“…In 8 studies, the parameters required to enter meta-analysis were not reported ( 27 34 ). In 2 studies, the findings related to epicardial thickness had been reported in groups other than CAD and non-CAD, such as coronary artery spasm ( 35 ) or carotid stenosis ( 36 ). In 8 studies, the numerical values of EFT had not been reported ( 31 , 36 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…Further, inconsistent measurement parameters hinder comparisons with preexisting literature. The prognostic value of EATV to diagnostic imaging has been shown in patients with moderate risk [11], those presenting with acute chest pain [10] and as part of the MESA study [20]. Clinical application of EAT volumetry without the use of automated means is cumbersome and time consuming, yet in direct comparison automated volumetry has demonstrated comparable results to manual segmentation [18,21].…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemically, EAT has been shown to differ from other fat tissue in concentration and production of inflammatory mediators resulting in infiltration by inflammatory cells and thus promoting the development of atherosclerosis [9]. Clinical application of EAT volumetry has been proven feasible and is expected to be of prognostic value by risk stratification of coronary artery disease (CAD) [8] and prediction of major adverse cardiac events [10,11].…”
Section: Introductionmentioning
confidence: 99%